The necrosis-inducing protein (NIP) gene contributes to Penicillium expansum virulence during postharvest pear infection. (August 2022) - Xu, Meiqiu; Zhang, Qidi; Dhanasekaran, Solairaj; Godana, Esa Abiso; Zhang, Xiaoyun; Yang, Qiya; Zhao, Lina; Zhang, Hongyin
Graphical abstract: Highlights: High-level NIP expression was observed during P. expansum infection. NIP was closely associated with genes related to plant CWDEs. NIP was functionally characterized by knockout and complementation. Δ NIP reduces sporulation and PAT accumulation via reduced mycelial production. NIP contributes to P. expansum virulence. Abstract: Penicillium expansum is the causative fungus of blue mold decay in postharvest pears resulting in substantial economic losses. Investigating P. expansum -pear fruit interactions is necessary to help develop P. expansum control strategies for effective and safe pear production. Investigating the P. expansum gene expression alterations and essential gene functions during the infection process is indispensable. Based on our results, the necrosis-inducing protein (NIP) gene was closely associated with genes related to plant cell wall degrading enzymes (CWDEs) and involved in P. expansum virulence. The NIP has high homology with other already-known fungal NIPs. To evidence the role of NIP in P. expansum virulence, NIP mutant (including knockout (Δ NIP ) and complementation mutant (c NIP )) P. expansum were generated. Despite the NIP deletion did not affect the basic morphology and structure of P. expansum, it slowed down the fungal growth and hyphal production, thus reducing P. expansum 's sporulation and patulin (PAT) accumulation. Furthermore, the deletion of NIP reduced the pathogenicity of P. expansum in pear. The complementation of NIP (c NIP ) restored the growth, conidia production, PAT accumulation, and virulence of Δ NIP to the level of wild-type P. expansum . In addition, PAT can cause decay and aggravate the disease severity of wild-type P. expansum and Δ NIP on pears. Our results confirmed NIP plays a crucial role in P. expansum 's growth, hyphal production, and pathogenicity in pears.